The Impact of Hybrid Learning on Student Engagement and Academic Performance in Post-Pandemic Science Education - Tri Yuni Hendrowati; M. Badrun; Siswoyo; Ana Istiani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to investigate the impact of hybrid learning models on student engagement and academic performance in science education at the elementary school level in the post-pandemic era. Conducted in 20 elementary schools across Lampung Province, the research examines how the integration of both in-person and online learning affects student involvement in science lessons and their academic outcomes. A mixed-methods approach was employed, combining quantitative data from student performance assessments and surveys on engagement, alongside qualitative insights from interviews with teachers and school administrators. The findings suggest that hybrid learning enhances student engagement by providing flexible learning environments, allowing students to access resources and participate in activities at their own pace. Additionally, the model has shown to improve academic performance, particularly in subjects requiring critical thinking and practical application, such as science. However, the study also highlights challenges such as unequal access to technology and the need for teacher training to effectively implecontribute ment hybrid methods. The results to understanding the evolving role of hybrid learning This study aims to investigate the impact of hybrid learning models on student engagement and academic performance in science education at the elementary school level in the post-pandemic era. Conducted in 20 elementary schools across Lampung Province, the research examines how the integration of both in-person and online learning affects student involvement in science lessons and their academic outcomes. A mixed-methods approach was employed, combining quantitative data from student performance assessments and surveys on engagement, alongside qualitative insights from interviews with teachers and school administrators. The findings suggest that hybrid learning enhances student engagement by providing flexible learning environments, allowing students to access resources and participate in activities at their own pace. Additionally, the model has shown to improve academic performance, particularly in subjects requiring critical thinking and practical application, such as science. However, the study also highlights challenges such as unequal access to technology and the need for teacher training to effectively implement hybrid methods. The results contribute to understanding the evolving role of hybrid learning in post-pandemic education and offer recommendations for optimizing its application in elementary science education.in post-pandemic education and offer recommendations for optimizing its application in elementary science education.